PERENCANAAN PENGGUNAAN SOLAR PANEL SEBAGAI SISTEM KELISTRIKAN PADA ALAT MEDIS MOBILE X RAY INSTALASI RADIOLOGI RUMAH SAKIT - M Yasir Pohan; Muhammad Naim; Harjuma; Aziz Asmauna (Jurnal Genta Mulia, 2026)
Mobile X-Ray is one of the tools used in hospitals as a key support for examining a disease. In emergency situations, the use of X-Ray equipment in remote areas becomes one of the problems, including the provision of electricity that can support the use of the equipment. With the difficulty of electricity in remote areas, a solution that can be used is the use of solar power plants (PLTS) that can be used without having to depend on electricity supplied by PLN. The use of solar power plants, in addition to being a solution to the difficulty of electricity in remote areas, is also a solution for saving costs in the long term. This step will support the transformation towards a more sustainable and inclusive health system. This study provides a foundation for further development in the implementation of solar-powered mobile X-ray equipment in hospitals and the health sector as a whole. This step will support the transformation towards a more sustainable and inclusive health system. This study provides a foundation for further development in the implementation of solar-powered mobile X-ray equipment in hospitals and the health sector as a whole.